A novel and nonderivatization method for the determination of valproic acid in human serum by two‐dimensional liquid chromatography. (10th September 2019) - Liu, Wei; Shang, Xiang; Yao, Shuyong; Wang, Feng
Abstract: A novel and robust two‐dimensional liquid chromatography with ultraviolet detection method (2D‐LC–UV) was developed and validated for high‐throughput determination of the concentrations of valproic acid (VPA) in human plasma. This 2D‐LC system was composed of a first‐dimensional LC column, a second‐dimensional LC column and an intermediate transfer column. The sample was directly injected into the 2D‐LC system after an easy protein precipitation treatment. After online preconcentration and primary separation by the first‐dimensional column, the target was captured by an intermediate column and then transferred to second‐dimensional column for analysis. The system transferred the target through "central cutting" mode whereby the drug peak was not subject to interference from the matrix. The analysis cycle time was completed within 7.0 min. Compared with other methods that have been developed, the analysis time was reduced and the operation was much easier without any derivatization. The calibration curve was linear over the 5.90–188.94 μg/ml range for the VPA concentrations. The intra‐day and inter‐day precisions were <5.6%. The recoveries were in the range from 95.2 to 98.0%. This method appears to be sensitive, precise, rapid and low‐cost for the quantification of VPA in serum sample.